Specialty Photonic Crystal Fibres and Their Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is intended to provide an overview of the state-of-the-art in specialty photonic crystal fiber technology and its multiple applications, combined with an optimistic outlook to what lies ahead. It comprises six original research papers and one review from different leading research institutions worldwide.